Preventing treatment spillover contamination in criminological field experiments: the case of body-worn police cameras - Ariel, Barak (Journal of experimental criminology, 2019)
A central issue in experiments is protecting the integrity of causal identification from treatment spillover effects. The objective of this article is to demonstrate a bright line beyond which spillover of treatment renders experimental results misleading. We focus on a highly publicized recent test of police body cameras that violated the key assumption of a valid experiment: independence of treatment conditions for each unit of analysis.